The intersection of colonialism and indentured labour in the Caribbean - Fergus, Claudius K. (The Palgrave handbook of Caribbean criminology, 2024)
Indentured labour was a peculiar invention of English colonisers in the seventeenth century, a pre-cursor to full-blown chattel slavery. When Caribbean plantocracies abandoned slavery in the nineteenth century they returned to indentureship to stabilise and expand the economy and create a barrier to freedmen’s progress. This second phase of indentured labour had the most profound impact on colonial society since the establishment of the sugar revolution. Only four polities did not participate: Puerto Rico, which avoided a sugar revolution; Barbados, which retained a viable white deficiency population and the only two independent states within the Caribbean Sea, Haiti and the Dominican Republic. Despite the inherent violence of the system, it was the foundation of the modern plural society of the Caribbean.